PERBEDAAN HASIL BELAJAR IPS SEJARAH ANTARA MODEL PEMBELAJARAN PETA KONSEP DENGAN MODEL PEMBELAJARAN CERAMAH BERVARIASI - Fransiska, Lya (Indonesian Journal of History Education, 2012)
This article intends to examine differences in learning outcomes of IPS history subject using a concept map of learning models compared with varied lectures penbelajaran models. Concept maps are applied in the experimental classes and lectures varied learning model is applied in the control class. The population in this study were all students in grade IX Kandeman SMP Negeri 1 year 2011/2012 which amounted to 240 students. Sampling was conducted using random cluster sampling and obtained class A as class IX experiments (learning model concept map) and the class of class IX B as a control (lecture learning models vary). Learning outcomes by using a learning model maps better than the concept of learning outcomes IPS History lecture on learning models vary. Advice and researchers hope that History Teachers can use the IPS model of learning a concept map as an alternative in the teaching of history to improve student learning outcomes and make learning history and social studies fun and interesting.